2023
DOI: 10.1080/21642850.2023.2170378
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the psychological wellbeing of women with gestational diabetes mellitus (GDM): increased risk of anxiety in women requiring insulin. A Prospective Longitudinal Observational Pilot Study

Abstract: Introduction Gestational diabetes mellitus (GDM) complicates ∼16% of pregnancies in Australia and has significant implications for health of both mother and baby. Antenatal anxiety and depression are also associated with adverse pregnancy outcomes. The interaction between GDM and mental health in pregnancy is poorly understood. With the aim of exploring the nuanced interaction between GDM and mental health further, we investigated whether GDM treatment modality (diet versus insulin) influenced psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…GDM can also cause psychological distress to the mother, which, in turn, affects the normal growth and development of the fetus. In a prospective longitudinal study, Fraser et al ( 13 ) found that the anxiety and depression scores of women with GDM who used insulin or who controlled their blood sugar through diet were significantly higher than those of women without GDM. Riggin et al ( 14 ) also found that GDM is associated with severe mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…GDM can also cause psychological distress to the mother, which, in turn, affects the normal growth and development of the fetus. In a prospective longitudinal study, Fraser et al ( 13 ) found that the anxiety and depression scores of women with GDM who used insulin or who controlled their blood sugar through diet were significantly higher than those of women without GDM. Riggin et al ( 14 ) also found that GDM is associated with severe mental illness.…”
Section: Introductionmentioning
confidence: 99%